Mechanistic study of NO oxidation on Cr-phthalocyanine: theoretical insight - Anchalee Junkaew (2018)
© The Royal Society of Chemistry. The reaction mechanisms of NO oxidation on chromium-phthalocyanine (CrPc) were elucidated using density functional theory calculations and compared with NO reduction. The results reveal that the reaction of NO oxidation on CrPc is a two-consecutive step pathway which produces NO 2 as a product. The first step can proceed through competitive Langmuir-Hinshelwood (LH) and Eley-Rideal (ER) mechanisms presenting the low activation barriers (E a ) in a range of 0.1 to 0.5 eV with exothermic aspects. Moreover, the ER mechanism is found to be more feasible. In the second step, the reaction requires an E a of 0.32 eV, which is considered as the rate determining step of the overall reaction. By comparing both NO oxidation and reduction, the results reveal that in the low O 2 system, CrPc converts NO to N 2 via a dimer (NO) 2 mechanism whereas in the excess O 2 system, it oxidizes NO to NO 2 easily. Both reaction systems required very low E a values, thus this low cost CrPc catalyst could be a candidate for NO treatment at room temperature.